The Influence Of Risk Management Committee And Family Ownership With Company Performance In Indonesia: Busy Directors As Moderating Variable - Ika Dewi Agustin; Cynthia Afriani Utama (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Corporate risk management and corporate governance have become important in managing the company. Both are believed to be able to reduce agency problems, between company owners and managers or between shareholders. Using a panel data regression analysis model, a sample of 602 non-financial public companies registered in Indonesia in the 2019-2021 period, this study focused on testing the effect of the existence of the Risk Management Committee and family share ownership on company performance ( ROA). The study also used busy directors as a moderating variable. The results showed that the existence of the Risk Management Committee had a positive and significant relationship with ROA. But family ownership has a negative and significant relationship with ROA. Meanwhile, the presence of commissioners who concurrently hold positions in other companies at once or busy directors, does not significantly affect the relationship between the Risk Management Committee and family ownership and the company's performance.